2022
DOI: 10.3390/ijerph19138165
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Literacy and Positive Mental Health in Adolescents: A Correlational Study

Abstract: This study aimed to assess adolescents′ Mental Health Literacy (MHL) level, Positive Mental Health (PMH) level, the association between sociodemographic variables and the MHL and PMH levels, and the relationship between adolescent′s MHL and PMH levels. A quantitative, cross-sectional, correlational study was conducted with a convenience sample of 260 adolescents studying in the 5th to 12th years of school. The Mental Health Knowledge Questionnaire, the Mental Health-Promoting Knowledge, and the Positive Mental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
(48 reference statements)
0
7
0
Order By: Relevance
“…Four instruments were used to collect data: (1) a sociodemographic data form with 8 variables (sex, age, marital status, number of children, education level, profession, work situation, and nationality); (2) the Appraisal of Self-care Agency Scale (ASA) Spanish validation [26], structured unidimensional into 24 items (16 positive and 8 negative) with questions 2, 6, 11, 13, 14, 15, 20, and 23 in reverse order to calculate the score, with four possible responses on a Likert-type scale with a cutoff of < 48 indicating low self-care (the lower the score, the less the capacity for self-care); (3) the PMHQ Positive Mental Health Questionnaire [19] based on the multifactorial model described above. The PMHQ has been validated in the Spanish population [27].…”
Section: Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Four instruments were used to collect data: (1) a sociodemographic data form with 8 variables (sex, age, marital status, number of children, education level, profession, work situation, and nationality); (2) the Appraisal of Self-care Agency Scale (ASA) Spanish validation [26], structured unidimensional into 24 items (16 positive and 8 negative) with questions 2, 6, 11, 13, 14, 15, 20, and 23 in reverse order to calculate the score, with four possible responses on a Likert-type scale with a cutoff of < 48 indicating low self-care (the lower the score, the less the capacity for self-care); (3) the PMHQ Positive Mental Health Questionnaire [19] based on the multifactorial model described above. The PMHQ has been validated in the Spanish population [27].…”
Section: Assessmentmentioning
confidence: 99%
“…The questionnaire yields a global PMH score ranging from 39 to 156, with a higher score indicating greater positive mental health, as well as specific scores for each factor which vary according to the number of items per factor. The inverted negative items are 4,23,25,37,5,21,22,26,15,16,17,27,28,29,32,35,36,11,18, and 20 (ordered by factor); and 4) an ad hoc form made up of 10 questions to assess variables relating to the participants' perception of the usefulness of the program, personal satisfaction with it, and overall assessment of the intervention. The instruments were administered at the outset and the conclusion of the program.…”
Section: Assessmentmentioning
confidence: 99%
“…Positive mental health status in adolescence is proportional to the level of MHL [ 20 ]. Recent worldwide MHL programs and effectiveness studies have reported an increase in youth MHL.…”
Section: The Effectiveness and Characteristics Of Mhl Programs For Ch...mentioning
confidence: 99%
“…On the other hand, MHL has three dimensions including recognition, knowledge, and attitude. Individuals with high MHL have the ability to know more about mental health and have positive attitude to cope with the psychological problems [13]. Tere may exist some potential mechanisms about the efect of psychological resilience and MHL on psychological distress.…”
Section: Introductionmentioning
confidence: 99%